2014
DOI: 10.1063/1.4886715
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation capacitance frequency dispersion of III-V metal-insulator-semiconductor devices due to disorder induced gap states

Abstract: Articles you may be interested inGate-control efficiency and interface state density evaluated from capacitance-frequency-temperature mapping for GaN-based metal-insulator-semiconductor devices Effects of interface states and temperature on the C -V behavior of metal/insulator/AlGaN/GaN heterostructure capacitors Interface states in polymer metal-insulator-semiconductor devices J. Appl. Phys. 98, 073710 (2005); 10.1063/1.2081109Characteristics of an indium antimonide metal-insulator-semiconductor structure pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 58 publications
4
35
0
Order By: Relevance
“…The border trap model is common for traditional III-V MOS system using GaAs, InP, and InGaAs. [35][36][37][38] In those cases, remarkable frequency dispersion at accumulation bias in the experimental C-V curves is the most characteristic feature for the border trap model. [35][36][37][38] Border traps have long time constants as they interact with the conduction band electrons via tunneling, leading to large frequency dispersion even at accumulation bias.…”
Section: à10mentioning
confidence: 99%
“…The border trap model is common for traditional III-V MOS system using GaAs, InP, and InGaAs. [35][36][37][38] In those cases, remarkable frequency dispersion at accumulation bias in the experimental C-V curves is the most characteristic feature for the border trap model. [35][36][37][38] Border traps have long time constants as they interact with the conduction band electrons via tunneling, leading to large frequency dispersion even at accumulation bias.…”
Section: à10mentioning
confidence: 99%
“…Under this consideration, interface states are located slightly far away from the dielectric/GaAs interface and can be modeled either as border traps in dielectrics near the MOS interface 51,52 or as disorder-induced gap states (DIGS) in semiconductors. 5,53 As shown in Figure 6, the incorporated nitrogen was distributed in the Al 2 O 3 layer with spatial width (identified as AlO x N y region) near the MOS interface. Its presence is believed to contribute to the reduction in accumulation dispersion.…”
Section: Characterization Of Electrical Properties Of Al 2 O 3 / Amentioning
confidence: 99%
“…52 In another study, Galatage et al identified defects in the semiconductor located within 0.8 nm from the surface as the origin of accumulation dispersion in In 0.53 Ga 0.47 As MOS capacitors. 53 In the present experiment, however, we should focuse on the semiconductor because only the nature of the semiconductor was altered. Thus, crystal orientation can impact on the trap states in GaAs located near the surface.…”
Section: F Influence Of Crystal Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…A distance (x) for the spatial location of the border traps relative to the In 0.53 Ga 0.47 As interface can be estimated using the relationship 33 x ¼ k lnðt=sÞ; (7) where k is the attenuation coefficient and t is the tunnelling time. Assuming a k value within the typical range of 9.8 Â 10 À9 -1.25 Â 10 À8 cm reported for the Al 2 O 3 / In 0.53 Ga 0.47 As interface [16][17][18]21,30 and considering that N CP saturation is reached at t $ 5 ls (Fig. 6), we obtain a distance x of about 1.6-2.1 Å from the interface.…”
Section: Transient Charging Time and Border Trap Responsementioning
confidence: 99%